2012
DOI: 10.1128/ec.00075-12
|View full text |Cite
|
Sign up to set email alerts
|

Tracing Putative Trafficking of the Glycolytic Enzyme Enolase via SNARE-Driven Unconventional Secretion

Abstract: Glycolytic enzymes are cytosolic proteins, but they also play important extracellular roles in cell-cell communication and infection. We used Saccharomyces cerevisiae to analyze the secretory pathway of some of these enzymes, including enolase, phosphoglucose isomerase, triose phosphate isomerase, and fructose 1,6-bisphosphate aldolase. Enolase, phosphoglucose isomerase, and an N-terminal 28-amino-acid-long fragment of enolase were secreted in a sec23-independent manner. The enhanced green fluorescent protein … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
31
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 57 publications
1
31
0
Order By: Relevance
“…However, the cellular mechanism responsible for transport of this primarily cytosolic housekeeping molecule to these atypical locations in an intact and enzymatically active form (enzyme activity requires GAPDH to be correctly folded and present as a tetramer) remains unknown. Because glycolytic enzymes do not contain any secretory signal sequence (24), it has long been postulated that such molecules are secreted via an unconventional secretory pathway (25, 26). In the current work, we demonstrate the role of Heat shock cognate 71 kDa protein (HSC70)‐mediated selective endosomal microautophagy in membrane trafficking of the cytosolic moonlighting protein GAPDH.…”
mentioning
confidence: 99%
“…However, the cellular mechanism responsible for transport of this primarily cytosolic housekeeping molecule to these atypical locations in an intact and enzymatically active form (enzyme activity requires GAPDH to be correctly folded and present as a tetramer) remains unknown. Because glycolytic enzymes do not contain any secretory signal sequence (24), it has long been postulated that such molecules are secreted via an unconventional secretory pathway (25, 26). In the current work, we demonstrate the role of Heat shock cognate 71 kDa protein (HSC70)‐mediated selective endosomal microautophagy in membrane trafficking of the cytosolic moonlighting protein GAPDH.…”
mentioning
confidence: 99%
“…For example, in several organisms, the synthesis of purine and CTP is promoted by the formation of protein complexes (47)(48)(49)(50). We previously found that recombinant enhanced GFP (EGFP) conjugated with N-terminal amino acid residues (aa 1 to 28) of yeast enolase (Eno2p) can form fluorescent foci in the cell (51). We speculated that the N-terminal (1 to 28) amino acid sequence might be the region regulating the intracellular localization of Eno2p.…”
mentioning
confidence: 99%
“…We speculated that the N-terminal (1 to 28) amino acid sequence might be the region regulating the intracellular localization of Eno2p. Full-length Eno2p conjugated with EGFP was localized uniformly in cells grown in an aerobic culture (51). If the N-terminal region of Eno2p participates in its localization, full-length Eno2p conjugated with fluorescent proteins would be expected to form foci under unknown environmental stimuli or during a specific phase of the cell life cycle.…”
mentioning
confidence: 99%
“…The DNA fragment encoding appS4 (FASMAC, Kanagawa, Japan) in pUC19 was amplified with primers 1 and 2, and the fragment was inserted into pULI1 (Miura et al, 2012) digested with EcoRI and XbaI using In-Fusion ® HD Cloning Kit (Clontech, Mountain View, CA, USA), resulting in pULS. DNA fragments encoding GLP1 or S 2 -GLP1 with or without a FLAG tag at the C-terminus were prepared by annealing of oligonucleotides with homologous region to pULS (FASMAC) ( Table 2).…”
Section: Name Sequencementioning
confidence: 99%